Blocking CD47 efficiently potentiated therapeutic effects of anti-angiogenic therapy in non-small cell lung cancer. Issue 1 (11th December 2019) - Zhang, Xuyao; Wang, Yichen; Fan, Jiajun; Chen, Wei; Luan, Jingyun; Mei, Xiaobin; Wang, Shaofei; Li, Yubin; Ye, Li; Li, Song; Tian, Wenzhi; Yin, Kai; et al.
Abstract : Background: Inhibitors targeting VEGF and VEGFR are commonly used in the clinic, but only a subset of patients could benefit from these inhibitors and the efficacy was limited by multiple relapse mechanisms. In this work, we aimed to investigate the role of innate immune response in anti-angiogenic therapy and explore efficient therapeutic strategies to enhance efficacy of anti-angiogenic therapy against non-small cell lung cancer (NSCLC). Methods: Three NSCLC tumor models with responses to VEGF inhibitors were designed to determine innate immune-related underpinnings of resistance to anti-angiogenic therapy. Immunofluorescence staining, fluorescence-activated cell sorting and immunoblot analysis were employed to reveal the expression of immune checkpoint regulator CD47 in refractory NSCLC. Metastatic xenograft models and VEGFR1-SIRPα fusion protein were applied to evaluate the therapeutic effect of simultaneous disruption of angiogenetic axis and CD47-SIRPα axis. Results: Up-regulation of an innate immunosuppressive pathway, CD47, the ligand of the negative immune checkpoint regulator SIRPα (signal regulatory protein alpha), was observed in NSCLC tumors during anti-angiogenic therapy. Further studies revealed that CD47 upregulation in refractory lung tumor models was mediated by TNF-α/NF-κB1 signal pathway. Targeting CD47 could trigger macrophage-mediated elimination of the relapsed NSCLC cells, eliciting synergistic anti-tumor effect. Moreover, simultaneously targeting VEGF and CD47 by VEGFR1-SIRPα fusion protein induced macrophages infiltration and sensitized NSCLC to angiogenesis inhibitors and CD47 blockade. Conclusions: Our research provided evidence that CD47 blockade could sensitize NSCLC to anti-angiogenic therapy and potentiate its anti-tumor effects by enhancing macrophage infiltration and tumor cell destruction, providing novel therapeutics for NSCLC by disrupting CD47/SIRPα interaction and angiogenetic axis.